O sistema Universidade Aberta do Brasil como política de expansão do ensino superior - Wunsch, Laura (2014)
This work has as theme the Open University of Brazil system (UAB, as the acronym in Portuguese) while public policy of stimulus for the modality of distance education (EAD, as the acronym in Portuguese) and expansion of public higher education which has been widely used especially in training programs and actions for teacher who work in basic education. The study aims understand to what extent actions on public policy are related to the expansion and consolidation of EAD in public higher education, considering the main effects from this system in two federal institutions of higher education of Rio Grande do Sul. The UAB, from the proposed of inserting of digital information and communication Technologies and development of EAD as a way to expand the supply and improve the quality of higher education, becomes an important subject of investigation in view of the need to analyze the route of such a policy and its effects in practice. The methodology was qualitative approach and corpus constituted by regulations and guidelines of UAB, as well as subjects responsible for policy implementation (managers, teachers and tutors). Bibliographical and documentary surveys were performed, and semistructured interviews with the subjects, utilizing content analysis (BARDIN, 2011) from the perspective of comparative education to identify how the same policy is being performed in two different scenarios. The theoretical referential is grounded by authors whose address issues related to the topic, such as Fainholc (2008), Pimentel (2006, 2010), Kenski (2003), Gatti et al. (2011), Muller e Surel (2002), among others. Can be perceived, in general, the UAB has produced many impacts in Brazilian higher education becoming apparent the one hand, many challenges to overcome and on the other the relevance and importance of such a policy through its contributions, mainly those relating to the expansion and internalization of public higher education.